그라비어 오프셋법에 의한 30/30μm 미세전극용 실버페이스트 물성연구 - 안석출; Suck Chul Ahn; 남수용; Su Yong Nam (한국화상학회지, 2015)
본 연구에서는 flake type hybrid silver powder와 poxy type hybrid binder로 그라비어 오프셋 인쇄용실버 페이스트를 제조하였다. 제조된 실버 페이스트로 그라비어 오프셋인쇄법을 이용하여 30/30㎛(line/space)를 연속적으로 300장 인쇄가 가능했다. 130℃에서 20분 동안 오븐에서 경화시켰을 때, 선저항은 약 10.4Ω㎝,연필경도는 4H였다. 결론적으로 본 연구의 결과는 터치 패널용 narrow bezel전극으로 사용 가능함을 알 수 있었다. In this research, we have developed silver paste for gravure offset printing with flake type hybrid silver powder and epoxy type hybrid binder. By gravure offset printing using the producted silver paste, 30/30㎛(line/space) continuously 300 sheets printing be possible. When cured in oven for 20 mintes at 130℃, line resistant was about 10.4Ω㎝, pencil hardness was 4H. In conclution, it found that this results can be narrow bezel electrode for touch panel.